GENOTOXIC AND MUTAGENIC EFFECTS OF DIFLUBENZURON, AN INSECT GROWTH REGULATOR, ON MICE - Barros, Aline Lima de; Souza, Vanessa Vilamaior de; Navarro, Stephanie Dynczuki; Oesterreich, Silvia Aparecida; Oliveira, Rodrigo Juliano; Leite Kassuya, Candida Aparecida; Arena, Arielle Cristina [UNESP] (Taylor & Francis Inc, 2013)
This study assessed the genotoxic and mutagenic potential of diflubenzuron (DFB) insecticide in mice. Mice were divided into five groups: group I: negative control; group II: positive control; group III: 0.3 mg/kg of DFB; group IV: 1 mg/kg of DFB; group V: 3 mg/kg DFB. Peripheral blood was collected for the comet assay and the micronucleus (MN) test. DFB increased incidence of comet formation at all doses tested. A rise in the frequency of MN in mouse peripheral blood was observed 24, 48, and 72 h postexposure at all doses tested. Data demonstrate that DFB exerts genotoxic and mutagenic effects in a dose-dependent manner.